Apotegmes de les "vitas patrum" catalanes - Columba Batlle, Lluís (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: Edition of a fragment of Verba seniorum by Pope Pelagius from a fourteenth century manuscript, which throws some light on the original Catalan ver